2004
DOI: 10.1055/s-2004-828891
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Bile Markers for Cholangiocarcinoma

Abstract: Surgery remains the only curative treatment option for cholangiocarcinoma (CC). Currently, both early identification of CC in affected individuals at high risk and accurate diagnosis of unexplained biliary strictures are problematic. However, growing insights into biochemical and molecular mechanisms underlying biliary carcinogenesis have suggested serum and bile markers for the diagnosis of CC. These tools include tumor antigens or products (e.g., carbohydrate antigen [CA] 19-9), cytokines (e.g., interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 102 publications
(160 reference statements)
5
108
1
Order By: Relevance
“…In a series of cholangiocarcinoma patients without PSC, the sensitivity of CA 19‐9 concentrations >100 U/mL in diagnosing cholangiocarcinoma was 53% 29. However, although CEA is also measured frequently, it has been reported to have unsatisfactory sensitivity and specificity for cholangiocarcinoma 30, 31. In the current study, elevated values of CEA were noted in 54.5% of mucinous cholangiocarcinoma patients.…”
Section: Discussioncontrasting
confidence: 42%
“…In a series of cholangiocarcinoma patients without PSC, the sensitivity of CA 19‐9 concentrations >100 U/mL in diagnosing cholangiocarcinoma was 53% 29. However, although CEA is also measured frequently, it has been reported to have unsatisfactory sensitivity and specificity for cholangiocarcinoma 30, 31. In the current study, elevated values of CEA were noted in 54.5% of mucinous cholangiocarcinoma patients.…”
Section: Discussioncontrasting
confidence: 42%
“…Their use in CC was recently evaluated by Nehls et al, 6 who reviewed 11 studies with over 1,200 patients resulting in an average sensitivity of 71% and 51% and an average specificity of 78% and 88% for CA19.9 and CEA, respectively. The superior discriminatory power of CEA is noted both in this study and in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Nonparametric univariate analysis of these peaks revealed that 14 were differentially expressed (P Ͻ .05): 4 were upregulated (m/z 9,760, 10,096, 10,311, and 11,664) and 10 were downregulated (m/z 5,078, 5,734,5,933,6,105,6,632,7,939,8,468,8,691,8,905, and 16,089) in the cancer subgroup. The single most significant peak with highest discriminatory power was at m/z 10,311 and was upregulated in the cancer group (P Ͻ .001; ROC AUC 0.89) (Fig.…”
Section: Tissue Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In patients with PSC and CC, a wide range of sensitivity (38-89%) and specificity (50-98%) of CA 19-9 has been reported. 3,9 Although serum CA 19-9 is the mainstay marker for the diagnosis of biliopancreatic malignancies, a persistent elevation can also be observed in various benign diseases with no evidence of malignancy. 14 In view of these drawbacks of CA 19-9, other circulating markers have been evaluated for diagnosis and prognosis of biliary malignancy, either alone or as a part of a biomarker panel.…”
Section: Introductionmentioning
confidence: 99%